PERANAN ASEAN SENIOR OFFICIALS ON DRUGS MATTERS (ASOD) DALAM MENANGGULANGI Drugs Trafficking DI NEGARA VIETNAM (2009-2013) - Tiara Sauqi; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research explains about how the ASOD's role of international organizations in addressing Drugs Trafficking in Vietnam (2009-2013). Drugs Trafficking is one of the transnational crime that threatens global security. Vietnam is a country that is becoming one of the world's gateway Drugs Trafficking in Southeast Asia. ASOD international organization founded in 1984 and has offices in nearly every ASEAN member countries, the main goal is to Southeast Asia Free Of Drugs In Terms Of Production, trafficking, and the abuse. In addition to government ASOD and Vietnam also have an obligation to meet the goal of drug-free program in 2015.This research used qualitative methods. In this research, the data was collected by using library research technique where this technique is collecting data sources from the literature. This research uses pluralism approach which this approach has assumption that actor in international relation isn't just a state but there’s another actor one of international organization. In this research, writer uses role theory, sekuritisasi theory, and international organization theory which each organization has their duty. This research if ASOD has important duties and roles to overcome Drugs Trafficking in Vietnam. To overcome this problem of Drugs Trafficking in Vietnam, ASOD have a role in establishing external cooperation both bilaterally and regionally within the framework of the ASEAN member countries, NGOs, and other relevant organizations. to approve a new program in achieving a regional ASEAN drugs free.Keywords : ASOD, ASEAN Drugs Free 2015, Drugs Trafficking, Vietnam